The Influence of the Problem Posing Learning Model on Students' Problem-Solving Abilities in History Learning for Class XI of SMA Negeri 11 Banjarmasin - Muslimah Muslimah; Melisa Prawitasari; Sriwati Sriwati (STKIP Taman Siswa Bima, 2025)
Problem-solving ability is a higher-order thinking skill that plays an essential role in history learning. However, students often face difficulties due to limited active engagement in the learning process. This condition encourages the application of learning models that can enhance such abilities. This study aims to describe the effect of the problem posing learning model on students’ problem-solving skills in grade XI at SMA Negeri 11 Banjarmasin. The research employed a quantitative method with a quasi-experimental design, specifically the nonequivalent control group design. The population consisted of all grade XI students, with purposive sampling used to select two classes: XI-C as the experimental group (problem posing) and XI-A as the control group (expository). The research instrument was a multiple-choice test, previously validated and tested for reliability. Results of the Independent Sample t-Test showed that the pretest significance was 0.364 (>0.05), while the posttest result was <0.001 (<0.05), with a t-value of 12.236 exceeding the t-table value of ±1.993 (df = 72, α = 0.05). These findings reject H0 and accept Ha, indicating that problem posing is more effective than expository learning. Thus, the problem posing model has a positive effect on improving students’ problem-solving skills in history learning.